Pengaruh Model Pembelajaran Contextual Teaching and Learning (CTL) Berbantuan E-LKPD untuk Meningkatkan Hasil Belajar Ekonomi Siswa SMA Negeri 1 Dawan - Ni Kadek Wina Febiyanti; Luh Indrayani (Jurnal Pendidikan Ekonomi Undiksha, 2025)
This study aims to determine the effect of the Contextual Teaching and Learning learning model assisted by E-LKPD to improve the learning outcomes of students in economics at SMA Negeri 1 Dawan. The type of research used is a quasi- experimental study "Posttest Only Control". The population in this study were all Class XI Economics at SMA Negeri 1 Dawan which consisted of 3 classes with a total of 105 students. The sampling technique in this study was the purposive sampling technique, obtained class XI.5 as many as 34 students as the experimental group and class XI.6 as many as 36 students as the control group. Data on students' economic learning outcomes were obtained by giving a posttest and analyzed using a t-test. The results of the hypothesis test showed that a significance value of 0.000 was obtained which was reduced from 0.05, it can be concluded that the test results reject H0 and accept H1. This study shows that the contextual teaching and learning learning model assisted by E-LKPD has a positive effect on the learning outcomes of students in economics at SMA Negeri 1 Dawan.